Correlation Between Coinfection of Severe and Critically Ill COVID-19 Patients In Intensive Care Unit with Leucocyte, Neutrophil, CRP, Procalcitonin and Length of Stay - Prayitno, Harman; Sugiri, Yani Jane; Astuti, Tri Wahju; Fatoni, Arie Zainul; Hastuti, Nurima Diyah Puji (Indonesian Society of Respirology (ISR), 2025)
Background: Severe or critical COVID-19 infections are linked to admissions in the intensive care unit (ICU), which increases the risk of coinfection and results in a worsened prognosis. This research seeks to evaluate the relationship between bacterial and fungal coinfection in COVID-19 and leukocyte, neutrophil, C-Reactive Protein (CRP), procalcitonin levels, length of stay, and outcome (whether the patient was discharged from ICU to the ward or died). Method: This research constitutes a retrospective cohort analysis. Data was collected from the medical records of patients admitted to the ICU of Saiful Anwar General Hospital in Malang from August 2020 to August 2021, who tested positive for COVID-19. A total of 352 individuals qualified according to the inclusion criteria. Results: Coinfection occurred in 22.2% of COVID-19 patients, with bacterial 84.61%, fungal 11.53%, and both bacterial and fungal 3.84%. The average stay for patients without coinfection was 6 days, while it was 13 days for those with coinfection. We also observed a rise in mortality rate for coinfection at 71.8% compared to 31% for non-coinfection. Coinfection with bacterial, fungal, or both types in COVID-19 shows a positive correlation with Leucocyte (P=0.001; r=0.356), Neutrophil (P=0.001; r=0.438), CRP (P=0.003; r=0.164) and Procalcitonin (P=0.001; r=0.192) as well as a positive correlation with the length of stay (P=0.001) and a negative correlation with the outcome (P=0.001). Conclusion: Coinfection occurred in just about one-fifth of COVID-19 patients. We suggest prescribing antimicrobials only when there is a compelling reason. Timely detection of bacterial and fungal coinfection was essential to identify high-risk patients and determine appropriate interventions to prevent longer hospital stays and reduce mortality.